The construction and testing of a macro-econometric forecasting model for the Greek economy - Yannopoulos, A. (1984)
This thesis concerns the construction and testing of an annual forecasting econometric model for the Greek economy between 1954 and 1977. The economic structure has been broken down into several subsectors and statistical analysis has been employed to determine the main factors explaining the relationships in each subsector.